Erector Spinae Block vs Paravertebral Block in Breast Cancer Surgery: A Systematic Review and Meta-analysis - Rizky Rahmad Tri Cahyo; Doso Sutiyono; Intan Karmila; Ismini Aufakamilia (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2025)
Background :The paravertebral block (PVB) is the gold standard for postoperative analgesia in breast surgery, but it easily causes pneumothorax. Erector spinae plane block (ESPB) is considered as alternative to PVB because its less invasive so relative safer. However, evidence in favor of these techniques is lacking. Method :A search of PubMed Central, Cochrane Library, Wiley Online Library, and ClinicalTrials.gov to identify the latest 20 years studies comparing ESPB and PVB in breast cancer surgery was conducted. Our endpoints were: intraoperative fentanyl consumption, total postoperative morphine, and time to first analgesic request. Result :A total of 6 studies (394 patients) were included for this meta-analysis. The pooled analysis showed there is -3.03 (MD = -3.03: 95% CI: -7.47– 1.42) mean difference with insignificant overall effect (P = 0.18) for intraoperative fentanyl consumption on ESPB patient after breast cancer surgery compared against PVB procedure. There is an insignificant between ESPB and PVB regarding total postoperative morphine with 0.46 (MD = 0.46: 95% CI: -0.94 – 1.85) mean difference with insignificant overall effect (P =0.52). There is a significant difference between ESPB and PVB regarding time to first analgesic request with 0.23(MD = 0.23: 95% CI: 0.01– 0.44) risk ratio with statistically significant overall effect (P = 0.04). Both intraoperative fentanyl consumption and total postoperative morphine consumption showed heterogeneity. Meanwhile, time to the first analgesic request showed no heterogeneity. Conclusion : PVB is superior to ESPB regarding time to first analgesic request, but ESPB can serve as analternative to PVB with a similar analgesic effect